Cell-to-cell transmission of HSV1 in human keratinocytes in the absence of the major entry receptor, nectin1. - Joanne Kite; Tiffany Russell; Juliet Jones; Gillian Elliott (PLoS Pathogens)
Herpes simplex virus 1 (HSV1) infects the stratified epithelia of the epidermis, oral or genital mucosa, where the main cell type is the keratinocyte. Here we have used nTERT human keratinocytes to generate a CRISPR-Cas9 knockout (KO) of the primary candidate HSV1 receptor, nectin1, resulting in a cell line that is refractory to HSV1 entry. Nonetheless, a small population of KO cells was able to support infection which was not blocked by a nectin1 antibody and hence was not a consequence of residual nectin1 expression. Strikingly at later times, the population of cells originally resistant to HSV1 infection had also become infected. Appearance of this later population was blocked by inhibition of virus genome replication, or infection with a ΔUL34 virus defective in capsid export to the cytoplasm. Moreover, newly formed GFP-tagged capsids were detected in cells surrounding the initial infected cell, suggesting that virus was spreading following replication in the original susceptible cells. Additional siRNA depletion of the second major HSV1 receptor HVEM, or PTP1B, a cellular factor shown elsewhere to be involved in cell-to-cell transmission, had no effect on virus spread in the absence of nectin1. Neutralizing human serum also failed to block virus transmission in nectin1 KO cells, which was dependent on the receptor binding protein glycoprotein D and the cell-to-cell spread glycoproteins gI and gE, indicating that virus was spreading by direct cell-to-cell transmission. In line with these results, both HSV1 and HSV2 formed plaques on nectin1 KO cells, albeit at a reduced titre, confirming that once the original cell population was infected, the virus could spread into all other cells in the monolayer. We conclude that although nectin1 is required for extracellular entry in to the majority of human keratinocytes, it is dispensable for direct cell-to-cell transmission.